Simulation study of pulse width modulation schemes for three-phase impedance source inverter - Mohammad Arif Khan; Shailesh Kumar Gupta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
To avoid a short circuit of the input direct current (DC). source, a 3-phase inverter cannot run two switches in the same leg at a time, and it always operates in buck mode, with the output voltage being less than the input voltage. The Impedance source inverter features a feature that allows both switches in one leg to operate at the same time, and it can operate in buck/boost mode, which means the output voltage can be greater than the input voltage depending on the shoot-through time. In the literature, there are a few pulse width modulation (PWM) techniques for Impedance source inverter control. This research includes a simulation study as well as an examination of existing PWM schemes in the literature, as well as a proposal for TESVPWM for inverters. The inverter performance has evaluated using total harmonic distortion and fundamental components, validating by simulation findings.